Gabion Wall Slope Stabilization for Pejagan – Prupuk Road Widening (STA 116+450) - Kesuma, Andhika; Lastiasih, Yudhi; Kurniawan, Ibnu; Wiharjito, Deni (Journal of Infrastructure & Facility Asset Management, 2023)
The Pejagan – Prupuk road section continues to experience an increase in the interest of motorists, especially goods vehicles. In order to anticipate escalation of the traffic volume, road widening need to be planned to increase road capacity. The widening of the Pejagan – Prupuk road section needs to be done carefully. Road widening is carried out at an elevation of 4 meters from the subgrade so that a fairly unstable slope of the road body will be formed. The slope of road widening are modelled without reinforcement by using a Limit Equilibrium Method (LEM) software.  It generate Factor of Saferty (FS) value of 0.84, which means the slope is in an unstable condition. Unstable embankment slopes could be treated with geotextile and gabion. Furthermore, these reinforcements were used to stabilize the embankment slope. Based on a reinforcement modeling, gabion combined with geogrid as an alternative reinforcement was able to increase FS of embankment slope more than 1.5.